A CLASSIFICATION OF THE CUBIC SEMISYMMETRIC GRAPHS OF ORDER 34p² - Mehdi Alaeiyan; Rasul Aramian (Journal of the Indonesian Mathematical Society, 2011)
A simple undirected graph is called semisymmetric if it is regular and edge transitive but not vertex-transitive. In this paper, we classify all connected cubic semisymmetric graph of order 34p², where p be a prime.DOI : http://dx.doi.org/10.22342/jims.17.1.9.11-15